2012
DOI: 10.4238/2012.september.17.2
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acid-induced milk fat reduction associated with depressed expression of lipogenic genes in lactating Holstein mammary glands

Abstract: ABSTRACT. The efficacy of conjugated linoleic acid (CLA) in diet supplements for milk fat reduction is well documented in several species. However, the mechanisms by which fatty acids regulate mammary lipogenesis remain largely unknown, especially with regard to gene expression of enzyme and regulators. In this study, 8 Holstein dairy cows in their mid-lactation period were randomly divided into 2 groups. Control cows received a Ca salt of palm oil fatty acid dietary supplement, and those in the CLA group were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The fatty acid composition in the milk samples of cows in the present study corresponded with the results obtained for dairy breeds. The most represented group of FAs in milk was SFA, followed by monounsaturated fatty acid (MUFA) and PUFA, which is consistent with the previous results (Carvajal et al, 2016;Hanuš et al, 2016;Vranković et al, 2017). Vranković et al (2017) showed a similar FA composition in the milk of Holstein cows (C10:0 = 3.053, C12:0 = 3.694, C14:0 = 12.33 vs. C10:0 = 3.00, C12:0 = 3.70, C14:0 = 12.03) at the 150th day of lactation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The fatty acid composition in the milk samples of cows in the present study corresponded with the results obtained for dairy breeds. The most represented group of FAs in milk was SFA, followed by monounsaturated fatty acid (MUFA) and PUFA, which is consistent with the previous results (Carvajal et al, 2016;Hanuš et al, 2016;Vranković et al, 2017). Vranković et al (2017) showed a similar FA composition in the milk of Holstein cows (C10:0 = 3.053, C12:0 = 3.694, C14:0 = 12.33 vs. C10:0 = 3.00, C12:0 = 3.70, C14:0 = 12.03) at the 150th day of lactation.…”
Section: Discussionsupporting
confidence: 92%
“…The feeding of dairy cows is the main factor impacting milk fat composition. Pasture intake reduces the concentration of saturated fatty acids (SFAs) in the milk of grazing cows (Couvreur et al, 2007;Frigo et al, 2015;Hanuš et al, 2016;Ponnampalamet al, 2018). Furthermore, genetic factors influence fatty acid (FA) variability.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that reduction of milk fat in response to feeding CLA is associated with altered MFG size. We used a rumen-protected product rich in trans-10,cis-12 CLA (Han et al, 2012) to induce MFD and measured MFG size using a laser particle size analyzer.…”
Section: Short Communicationmentioning
confidence: 99%
“…Other studies were also considered but not included in the evaluation because they did not satisfy one or more of the criteria: Bell & Kennelly (2003), Hutchinson et al (2012), Moallem et al (2010) and Piperova et al (2004) reported milk FA concentrations only for FA of between 14 and 18, 12 and 22, 12 and 20, and 14 and 20 carbon atoms, respectively;Loor & Herbein (2003) only infused CLA for 48 h and collected milk samples directly after infusion had stopped;Viswanadha et al (2003) applied CLA intravenously;Moore et al (2005) investigated the effects of CLA on heat-stressed cows;Hun et al (2012) did not report the DMI of the animals and Pappritz et al (2011) reported pooled milk FA concentrations and DMI which was not recorded simultaneously with milk samples for FA analyses such that milk FA composition could not be related to DMI.Hötger et al (2013) did not report the total milk fat yield of the animals;Huang et al (2008) did not report how much trans -10, cis -12 CLA was administered to the cows; andMedeiros et al (2010) used crossbred Holstein x Zebu cows, Shingfield et al (2009) used Finnish Ayrshire cows and Sigl et al (2010) used Brown Swiss cows instead of Holstein cows and thus, dietary effects on milk component synthesis might be overlaid or masked by inter-breed differences (Stoop et al 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Hun et al (2012) did not report the DMI of the animals and Pappritz et al (2011) reported pooled milk FA concentrations and DMI which was not recorded simultaneously with milk samples for FA analyses such that milk FA composition could not be related to DMI.…”
Section: Methodsmentioning
confidence: 99%